Data Profiling in Cloud Migration: Data Quality Measures while Migrating Data from a Data Warehouse to the Google Cloud Platform - Cabral, Andreia Filipa Gonçalves (2021)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics